2020
DOI: 10.1155/2020/8862600
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Bilateral Rupture of the Patellar Tendon and Medial Collateral Ligament: A Case Report and Literature Review

Abstract: Bilateral rupture of the patellar tendon is considered an uncommon and rare musculoskeletal injury. The association of this lesion with medial collateral ligament tear appears to be exceedingly rare. We present the case of a combined rupture of the medial collateral ligament (MCL) and the patellar tendon of both knees in a 48-year-old man, after falling 2 meters down an embankment. While there are numerous publications concerning associated MCL tears and other knee ligaments, a combination of MCL tear with a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…We found that patients with bilateral ruptures can expect to return to their normal baseline mobility, including a return to sports by 6–12 months post-operatively. Three patients had returned to their baseline level of mobility by six months post procedure [2] , [4] , [7] . Only one patient had a documented post-operative complication, with Taylor et al's patient developing a pulmonary embolism on post operative day 1, however they were successfully treated with heparin [5] .…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…We found that patients with bilateral ruptures can expect to return to their normal baseline mobility, including a return to sports by 6–12 months post-operatively. Three patients had returned to their baseline level of mobility by six months post procedure [2] , [4] , [7] . Only one patient had a documented post-operative complication, with Taylor et al's patient developing a pulmonary embolism on post operative day 1, however they were successfully treated with heparin [5] .…”
Section: Discussionmentioning
confidence: 96%
“…We limited our search to full text, English language publications for adult patients. We excluded studies in patients with risk factors present for tendon rupture, which yielded 17 suitable case reports ( Table 1 ) [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] . Of note, there were three paediatric cases in the literature, one of which had a known diagnosis of Ehlers-Danlos syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…La búsqueda incluyó publicaciones de texto completo en inglés o español. Excluimos estudios de pacientes con factores de riesgo o donde no se detallaran en específico las características del caso clínico, lo que dejó 13 reportes de caso para el análisis 4,10,19,[25][26][27][28][29][30][31][32][33][34] (Tabla 1).…”
Section: Similitudes Y Diferencias Con Otros Estudiosunclassified
“…Reforzado con alambre Kamienski, et al 30 43 Masculino Movimiento giratorio jugando softbol 1/1 Reparación primaria con tres túneles transóseos con sutura FiberWire Moura, et al 31 34 Masculino Desaceleración súbita asociado a movimiento de torsión 1/1 Reparación primaria término-terminal con técnica Kessler reforzado con suturas intraóseas. Protegido temporalmente con cerclaje e inmovilizado con yeso circular Cibula, et al 32 44 Masculino No específica mecanismo 1/1 Reparación primaria con túneles transóseos con FiberWire y protección con cerclaje de alambre Foley, et al 33 47 Masculino Caída jugando fútbol 1/1 Reparación primaria con InternalBrace, anclas SwiveLock y aumento con sutura continua Louka, et al 34 48 Masculino Caída de dos metros de altura 1/1 Reparación primaria con tres anclas con suturas con técnica Krakow, reforzado con alambre 1.2 mm y aumento con tendón cuadricipital dos opciones han demostrado propiedades biomecánicas similares o incluso superiores en favor de las anclas, debido a una menor separación del sitio de la reparación y a una mejor resistencia a la carga cíclica. 22,40 De acuerdo con Courtney y colaboradores, la ubicación de la lesión puede determinar el tipo de reparación; se puede realizar una reparación transósea en casos de avulsión proximal o una reparación con anclas en casos de avulsión distal.…”
Section: Autorunclassified